I'm Growing Up - Legaspi, NH (Likhaan: The Journal of Contemporary Philippine Literature; Vol 17 No 1 (2023): LIKHAAN 17: The Journal of Contemporary Philippine Literature, 2023)
This story follows sixteen-year-old Helen after her family’s sudden move from Tuguegarao to Cagayan de Oro. Her brother Jimmy runs away from their new home but often visits Helen at school. Helen struggles to balance duties for her parents, the social score with her new friend Bonnie, and her tough love for her brother, and the story explores the lengths one sibling will go to protect or chastise another.